(Study on the Effects of Agitating Duration and the Ration of Sulfuric Acid on the Preparation of Sulphated Shark Liver Oil as Fat Liquor) - Endah Djubaedah; Achmad Moestafa; Raoda Hafid; Abdul Aziz Darwis (Warta Industri Hasil Pertanian, 2003)
Study on the effects of agitating duration and the ratio of sulphuric acid on the preparation of sulphated shark oil as fat liquor had been carried out .the aimof the experiment was to introduce sulphuric acid that will be absorbed into the molecule chain of fatty acid cpmpletely and produced sulphated oil .the experiment was conducted in there variables of agitating duration (A) i.e:4,5 and 6 hours and the ration of sulphuric acid introduced and the ration of acid/oil was : agitationfor 6 hours and 40% of sulphuric acid ration or A3B3 combination .the sulphated oil has 96.77 lodine number saponification number 209.68 and 1.665 fixed S03 .the lower lodine number showed most double bond chain of the oil had been occupied by sulphate groups ,the higher saponification numbershowed the amout of sulphate group in the fatty oil chain ,the same as showed by the fixed S03 .it is concluded that agitating duration or mixing time and ratio sulphuric  acid to the shark liver oil to give significant effect on sulphated shark liver oil formed.